ANALISIS PEMERIKSAAN KAPAL OLEH MARINE INSPECTOR PADA KSOP KELAS IV PROBOLINGGO - Yudhi Setiyantara; Yudhanita Pertiwi; Ningrum Astriawati; Ade Chandra Kusuma; Ilham Pratama Putra (Majalah Ilmiah Gema Maritim, 2022)
In determining the seaworthiness of the ship, ship inspection is very important to do. KSOP has a very important role in determining the seaworthiness of ships. This study aims to determine the role of marine inspectors in ship inspection at KSOP Class IV Probolinggo. The research used qualitative descriptive methods. Data collection was carried out by surveys and interviews. The results of this study show that the marine inspector has the role and task of preparing to discuss the formulation and implementation of policies, standards, norms, guidelines, criteria, and procedures as well as technical guidance, evaluation, certification, and reporting in the fields of ship design, measurement, construction and stability of ships, nautical, technical, and radio as well as equipment and equipment for ship safety and equipment as well as prevention of pollution from ships and management of ship safety and operation for ships indonesian flags that sail in Indonesian and international waters for all types of ships and all sizes. In the duties of inspection and measurement of ships carried out in the Legal Status and Certification of Ships section, carry out inspection tasks at the Port of Probolinggo. The results of the survey of the marine administration examination and physical examination were obtained that it took an average of 32.57 minutes.